Limited effects of plant-beneficial fungi on plant volatile composition and host-choice behavior of Nesidiocoris tenuis - Meesters, Caroline; Weldegergis, Berhane T.; Dicke, Marcel; Jacquemyn, Hans; Lievens, Bart (Frontiers in Plant Science, 2024)
Biological control using plant-beneficial fungi has gained considerable interest as a sustainable method for pest management, by priming the plant for enhanced defense against pathogens and insect herbivores. However, despite promising outcomes, little is known about how different fungal strains mediate these beneficial effects. In this study, we evaluated whether inoculation of tomato seeds with the plant-beneficial fungi Beauveria bassiana ARSEF 3097, Metarhizium brunneum ARSEF 1095 and Trichoderma harzianum T22 affected the plant's volatile organic compound (VOC) profile and the host-choice behavior of Nesidiocoris tenuis, an emerging pest species in NW-European tomato cultivation, and the related zoophytophagous biocontrol agent Macrolophus pygmaeus. Results indicated that fungal inoculation did not significantly alter the VOC composition of tomato plants.However, in a two-choice cage assay where female insects were given the option to select between